Learning about COVID-19 across borders: public health information and adherence among international travellers to the UK. (February 2022) - Cai, S.; Zhang, T.; Robin, C.; Sawyer, C.; Rice, W.; Smith, L.E.; Amlôt, R.; Rubin, G.J.; Yardley, L.; Hickman, M.; Oliver, I.; Lambert, H.
Abstract: Objective: Public health control measures at borders have long been central to national strategies for the prevention and containment of infectious diseases. Travel was inevitably associated with the rapid global transmission of COVID-19. In the UK, public health authorities tried to reduce the risks of travel-associated spread by providing public health information at ports of entry. This study investigates risk assessment processes, decision-making and adherence to official advice among international travellers, to provide evidence for future policy on the provision of public health information to facilitate safer international travel. Study design: This study is a qualitative study evaluation. Method: International air passengers arriving at the London Heathrow Airport on scheduled flights from China and Singapore were approached for interview after consenting to contact in completed surveys. Semi-structured interviews were conducted by telephone, using two topic guides to explore views of official public health information and self-isolation. Interview transcripts were coded and analysed thematically. Results: Participants regarded official advice from Public Health England as adequate at the time, despite observing differences with intervention measures implemented in their countries of departure. Most participants also described adopting precautionary measures, including self-isolation and the use of face coverings that went beyond official advice, but reported adherence to guidance on contacting health authorities was more variable. Adherence to the official guidance was informed by the perceived salience of specific transmission possibilities and containment measures assessed in relation to participants' local social and institutional environments. Conclusion: Analysis of study findings demonstrates that international air travellers' responses to public health advice constitute a proactive process of risk assessment and rationalised decision-making to guide preventive action. This process incorporates consideration of the current living situation, trust in information sources, correspondence with cultural logics and willingness to accept potential risk to self and significant others. Our findings concerning international passengers' understanding of, and compliance with, official advice and mitigation measures provide valuable evidence to inform future policy and generate recommendations on the presentation of public health information to facilitate safer international travel. Access to a central source of regularly updated official information would help minimise confusion between different national guidelines. Greater attention to the differentiated information needs of diverse groups in creating future public-facing guidance would help to minimise the uncertainties generated by the receipt of generic information.